L'otage: Drame en trois actes - Claudel, Paul, 1868-1955 (Salt Lake City, UT : Project Gutenberg, 2016)
"L'otage: Drame en trois actes" by Paul Claudel is a three-act play published in 1911. Set during the final years of the French Empire from 1810 to 1814, it marks the first installment of Claudel's Trilogie des Coûfontaine. The play captures a turbulent moment in French history as Napoleon's empire crumbles. Staged repeatedly throughout the twentieth century, from London to Paris, this work has endured as a significant piece of French theatrical literature, later followed by two companion plays that complete the trilogy. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/L%27Otage Wikipedia page about this book: https://fr.wikipedia.org/wiki/L%27Otage
Release date is 2016-01-23
Produced by Winston Smith. Images provided by The Internet Archive.
Keywords: French drama -- 20th century